Waste to Masterpiece: Community Service in Wood Waste Management at Mojowarno Jombang - Akhsan, Miftakhul; Sari, Vivin Indah; Sopingi, Imam; Rahmawati, Siti (Jurnal Al Maesarah, 2024)
Wood waste management is an important issue in the Mojowarno Jombang area, due to the high production of waste from the wood processing industry while its utilisation is only for firewood. This service aims to increase community awareness about the utilisation of wood waste into economically valuable products, while reducing negative impacts on the environment. The service partners include small and medium enterprise (SME) groups and local communities active in the handicraft industry. The method used is socialisation and technical training on processing wood waste into creative products such as handicrafts and economic goods. The training covers basic processing techniques, product design, and marketing. The results showed an increase in community skills and understanding in managing wood waste, as well as an increase in income through the sale of processed products. In conclusion, this service successfully created a circular economy model in Mojowarno by utilising wood waste into value-added products. This result is important because it shows that a community-based approach to waste management can be an effective solution to environmental and local economic problems. This service is expected to be an example for other areas with similar problems.